Botulinum toxin in the management of myalgia in temporomandibular disorders: are all injections equal?. Issue 1 (January 2023) - Anwar, Haleemah; Attard, Alan; Green, Jason; Elledge, Ross O.C.
Abstract: Botulinum toxin (BTX) is becoming widely used as an adjunct to conservative management of myalgia-predominant temporomandibular disorders (TMDs) with reports of improved quality of life. There is, however, no consensus on the optimal dosage. Based on previous studies, dose regimens vary between clinicians, and we know of no standard dose protocol for the administration of BTX for the purpose of TMD management. A survey was sent to members of the British Association of Oral and Maxillofacial Surgeons (BAOMS) Temporomandibular Joint Sub-Specialty Interest Group (TMJ SSIG) and an international mailing list of high-volume TMJ surgeons (the TMJ Internetwork) to ascertain variations in dose regimens between different clinicians. The survey found that 41 respondents offered BTX to patients. The masseter muscle group was the most commonly injected site, and the majority of respondents (34/41) used Botox® (Allergan). Brands less commonly used included Dysport® (Ipsen), and Xeomin® (Merz Pharma). Botox® doses varied between 30 and 100 units, whilst Dysport® doses ranged from 50 - 300 units/muscle. The number of injection sites/muscle also varied. This survey demonstrates the wide variation in practice amongst clinicians with respect to BTX administration. To ensure optimal dose and response titration, further studies and evidence-based research are needed to standardise its use for the treatment of TMDs.